Brahmi: Nature’s Gift to Memory Enhancement in Pharmaceutical Sciences - Ujwal Vyas (Asian Journal of Pharmaceutics (AJP), 2025)
For Bacopa monnieri, the ancient medical system used the terms Brahmi and water hyssop. As a brain tonic in the past, it was used to improve memory and learning help treat epileptic or anxiety issues. In addition, the plant has been utilized to treat heart problems, digestive issues, and bronchoconstriction-related respiratory issues. Bacosides A and B are present in Brahmi, and the primary alkaloid is Brahmin. Nicotine is also present. In addition to D-mannitol, the Brahmi plant has other vital ingredients including potassium salts, hersaponin, and Bacoside A and B. We focus our discussion in this study on the chemical structure, pharmacological characteristics, and scientific studies that substantiate the claims made in Ayurveda that are not just limited to its traditional applications. Older persons who have Alzheimer’s disease (AD) suffer from a neurological illness. The significant rise in its incidence has forced the creation of more modern medications. Because of their biosafety profile and potential benefit for treating cognitive impairment, Ayurvedic herbal medicines are being studied more and more. In this post, we provide a critical analysis of one such Medhya Rasayana (nootropic medication) that is made with Bacopa monnieri extract (EBm). Brahmi is a good brain tonic and it can be taken at any age.